‘One Health’ in Action Series: Nos 1-8 - Laura H. Kahn, MD, MPH, MPP (Veterinaria Italiana, 2009)
This series of short articles was published in 2007 and distributed to the Kahn-Kaplan-Monath ‘One Health’ email distribution list. The articles are further examples of historical achievements obtained across numerous scientific disciplines, including human and veterinary medicine. Each article was written and developed with assistance from the Kahn-Kaplan-Monath ‘One Health’ team.The expanding ‘One Health’ email distribution list now totals approximately 590 individuals in 38 countries including Argentina, Australia, Bangladesh, Bahrain, Belgium, Belize, Bosnia and Herzegovina, Brazil, Canada, China, Colombia, Costa Rica, Croatia, France, Germany, Grenada, India, Indonesia, Israel, Japan, Malta, The Netherlands, Nepal, New Zealand, Nigeria, Norway, Portugal, Puerto Rico, Senegal, South Africa, Sri Lanka, Sweden, Switzerland, Thailand, Turkey, United Kingdom, United States and Uruguay.The list of supporters currently totals 417. If these lists are still being actively maintained by the publication date of this ‘One Medicine -One Health’ monograph, any allied health scientist, physician, osteopath or veterinarian may be added to one and/or both lists by contacting us at bkapdvm@verizon.net. Please include your curriculum vitae or brief biography, title, degree(s), affiliation and address consistent with those currently acknowledged as ‘One Health - One Medicine’ supporters. There are no obligations attached to joining this group and you may have your name removed at any time upon request.Those who have prepared this message and the two lists act independently of any other entity or organisation. However, where feasible, we attempt to augment and support those organisations' efforts to recognise, promote and implement this initiative, such as the American Veterinary Medical Association, American Medical Association, Society for Tropical Veterinary Medicine, Croatian Society for Infectious Diseases, American Society of Tropical Medicine and Hygiene, World Association of Veterinary Laboratory Diagnosticians, Delta Society, American Association of Veterinary Laboratory Diagnosticians, American Phytopathological Society, Association of American Veterinary Medical Colleges, Association of Schools of Public Health, American Society for Microbiology, National Association of State Public Health Veterinarians, Council of State and Territorial Epidemiologists, Association of Academic Health Centers, Association of American Medical Colleges and Immuno Valley Consortium in The Netherlands.This autonomous endeavour has been maintained pro bono due to our firm conviction regarding the enormous value of the ‘One Medicine - One Health’ concept.